Análisis a los Estados Financieros en la empresa Ediloja Cía. Ltda. de la ciudad de Loja. Períodos 2020-2021. - Medina Peñaranda, Adriana Yamilex (2023)
The Curricular Integration Assignment ANALYSIS OF THE FINANCIAL STATEMENTS IN THE COMPANY EDILOJA CÍA. LTDA. OF THE CITY OF LOJA. PERIODS 2020- 2021, was developed with the purpose of fulfilling both the general and specific objectives of analyzing the financial-economic situation of the Company Ediloja Cía. Ltda., for the periods 2020 – 2021, through vertical and horizontal analysis and financial indicators. In compliance with the proposed objectives, a Financial Diagnosis of the company was made, where it was possible to show that, although they keep an orderly control of their accounts, they do not carry out a financial analysis. Regarding the application of vertical analysis, it was evidenced that within the structure of the company Ediloja Cía. Ltda., has 68.44% (2020) and 66.71% (2021) of its assets concentrated in current assets, highlighting the Current Tax Assets that represent 30.56% of its structure, which are not contributing to improve the financial economic situation of the company because those responsible are not doing their job, which is to collect and not get into debt with the $180,412.30 in liabilities that the company has, finding financial solutions to pay in the bulky salaries that are in the account of wages. In the same way, it was evidenced that the creditors have the participation of 89.11% (2020) and 93.72% (2021) of the company and the shareholders, for their part, own 10.90%. (2020) and 6.28% (2021), due to the indebtedness that the company has. The application of the horizontal analysis presents an increase in the components: Revenues, Costs and a decrease in the components: Expenses, Profit/Loss of the Income Statement, the local provision of services as the account with the highest representation in revenues had a growth of 4 .62% between the periods, which is directly affected by the Net Loss for the period, which decreases by 85.72%. Financial indicators of liquidity, activity, indebtedness and profitability were applied, it was evidenced that, although the company does not generate profit, it has sufficient liquidity to cover its short-term obligations, in 2020 (1.62) and in 2021 (1.64). The account receivable turnover shows that the collection policy is deficient, because clients fulfill their obligations between 253 to 817 days, on the other hand, the company has a low level of indebtedness, in 2020 with 0.89 times and in 2021 with 0.94 times; Regarding the profitability indicators, it was found in all these common factors, that is, in the inventory rotation that occurs 5 approximately 1 to 4 times per year, sales policies should be implemented, since the relationship is directly proportional , the more sales, the more inventory turnover and likewise more turnover of accounts receivable, where the company also makes sales on credit. Finally, a financial analysis report was prepared, determining its financial and economic structure, obtaining conclusions and recommendations according to the results obtained that will help timely decision-making to improve the development of the company.